2008
DOI: 10.1088/0031-9155/53/18/017
|View full text |Cite
|
Sign up to set email alerts
|

A practical exposure-equivalent metric for instrumentation noise in x-ray imaging systems

Abstract: The performance of high-sensitivity x-ray imagers may be limited by additive instrumentation noise rather than by quantum noise when operated at the low exposure rates used in fluoroscopic procedures. The equipment-invasive instrumentation noise measures (in terms of electrons) are generally difficult to make and are potentially not as helpful in clinical practice as would be a direct radiological representation of such noise that may be determined in the field. In this work, we define a clinically relevant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…5 B), and because of this, adjacent detection events are spatially correlated. Blurring degrades spatial resolution, but the spatial correlation it produces filters noise (56)(57)(58)(59). Thus, the grayscale S/N may be greater than that expected from Poisson statistics, despite the added noise of the gain process, as our data show.…”
Section: Cellular Measurements Of Tb(iii)-mediated Fretmentioning
confidence: 47%
“…5 B), and because of this, adjacent detection events are spatially correlated. Blurring degrades spatial resolution, but the spatial correlation it produces filters noise (56)(57)(58)(59). Thus, the grayscale S/N may be greater than that expected from Poisson statistics, despite the added noise of the gain process, as our data show.…”
Section: Cellular Measurements Of Tb(iii)-mediated Fretmentioning
confidence: 47%
“…We present a historical overview of the methods used by Varian 9,15,16 , as well as an introduction and discussion of alternate methods introduced by Yadav and Rudin, et al 8,10 to determine the quantum-limited dose. The QLD and NED metrics are based on fundamentally similar principles.…”
Section: Theory Of Methodsmentioning
confidence: 99%
“…In the absence of a formal standard, we found that Yadav, et al 8 provides an excellent overview of previous works [9][10][11][12][13][14] to determine the quantum-limited operation range, while at the same time proposing a new metric 10 . The metric describes a new total-noise formalism to determine the lower end-point of the quantum-limited operation range which is named the instrumentation-noise-equivalent-exposure (INEE).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The heart of the MAF is the light image intensifier (LII) that enables the MAF to exhibit large variable gain. This large variable gain provides quantum-limited operation with effectively no additive instrumentation noise [12], [13]. The MAF is currently being evaluated as an EI X-ray transmission imager in a local hospital and providing encouraging results [10].…”
Section: Introductionmentioning
confidence: 99%